2024
DOI: 10.1039/d3ra07558c
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of super reductive EDA photocatalyst for challenging reactions: a theoretical and experimental study

Yi-Hui Deng,
Qini Li,
Manhong Li
et al.

Abstract: We have developed a novel electron-donor-acceptor (EDA) photocatalyst through DFT-guided design. This photocatalyst is formed in situ from isoquinoline, a diboron reagent, and a weak base, and can be effectively utilized for challenging reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Our group has recently described several strategies for generating aryl radicals under visible-light catalysis [39][40][41], and our previous studies have demonstrated that the reductive coupling of isoquinoline and B 2 Pin 2 can produce a dimer. This dimer can coordinate with an organic base (NEt 3 ) in situ to form an EDA complex (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently described several strategies for generating aryl radicals under visible-light catalysis [39][40][41], and our previous studies have demonstrated that the reductive coupling of isoquinoline and B 2 Pin 2 can produce a dimer. This dimer can coordinate with an organic base (NEt 3 ) in situ to form an EDA complex (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%